Return to basketball play following COVID-19 lockdown - Zacharakis, E. D.; Travlos, A. K.; Souglis, A. (Sports, 2021)
Due to concerns regarding the spread of coronavirus (COVID-19), major sporting events and activities have been temporarily suspended or postponed, and a new radical sports protocol has emerged. For most sports there are few recommendations based on scientific evidence for returning to team-game activities following the lifting of COVID-19 restrictions, the extended duration of lockdown, and self-training or detraining in the COVID-19 environment, and this is especially true for basketball. A post-lockdown return to the basketball court ultimately depends on the teams - coaches, trainers, players, and medical staff. Nevertheless, our current scientific knowledge is evidently insufficient as far as safety and return-to-play timing are concerned. This situation presents a major challenge to basketball competition in terms of organization, prioritization, maintaining physical fitness, and decision-making. While preparing an adequate basketball return program, the players` health is the major priority. In this article we briefly discuss the topic and propose multiple strategies.